ANALISIS TINGKAT KEPUASAN KONSUMEN: BUKTI EMPIRIS PADA HOTEL LIDO GRAHA LHOKSEUMAWE - Hismendi, Hismendi; Nur, M; Jayanti, Ery (Universitas Jabal Ghafur, 2024)
ABSTRACT The purpose of this research is to determine the factors that influence the level of consumer satisfaction at the Lido Graha Lhokseumawe Hotel. The research review carried out from the dimension of providing quality service is the commitment and responsibility of the management and all employees of the Lido Graha Hotel, especially in customer service who directly provide services to customers regarding all the facilities at the hotel. The analysis method is Ordinary Least Square (OLS). The results of the research findings show that the simultaneous test or F test on the tangible, reliability and responsiveness variables simultaneously has a significant effect on the customer satisfaction variable. Based on the partial test or t test, it shows that the reliability variable partially has a significant effect on customer satisfaction, while the values of the tangible and responsiveness variables have an influence but are not significant on customer satisfaction. We suggest to the management of the Lido Graha Lhokseumawe Hotel to pay attention to the room decoration and improve employees in providing responsive and fast service to their customers. Keywords:, Tangible, Reliability, Responsiveness, consumer satisfaction